MEMAHAMI LEGALITAS REMIX & PARODI DI SOSIAL MEDIA; MENGKAJI AMBIGUITAS UU HAK CIPTA TERHADAP KONTEN BERBASIS KEBEBASAN BERKARYA - Salsabila, Aulia; Franciska, Wira; Candra, Mardi (SINERGI : Jurnal Riset Ilmiah, 2025)
The evolution of digital culture has fostered the emergence of transformational content—such as remixes and parodies—as legitimate forms of creative expression. However, Indonesia’s copyright framework, particularly Article 44 of Law No. 28 of 2014, remains normatively ambiguous and fails to ensure legal certainty for such expressions. Employing a normative legal approach, this study identifies a structural tension between the protection of exclusive rights and freedom of expression, exacerbated by formalistic state enforcement and algorithmic content moderation by digital platforms that lack contextual assessment. This research recommends a reformulation of the “fairness” clause grounded in the fair use doctrine, along with the development of adjudicative mechanisms that safeguard substantive digital justice.